Mechanism for Improved Quality B[subscript]12As[subscript]2 Epitaxial Films on (0001) 4H-SiC Substrates Offcut towards [1-100] - Zhang, Yu; Chen, Hui; Dudley, Michael; Zhang, Yi; Edgar, James H.; Gong, Yinyan; Bakalova, Silvia; Kuball, Martin; Zhang, Lihua; Su, Dong; Kisslinger, Kim; Zhu, Yimei (Materials Research Society, 2010)
Epitaxial growth of icosahedral boron arsenide (B[subscript]12As[subscript]2, abbreviated here as IBA) on 4HSiC substrates intentionally misoriented from (0001) towards [1-100] is shown to eliminate rotational twinning. Comparisons of IBA on on-axis and off-axis c-plane 4H-SiC by synchrotron white beam x-ray topography (SWBXT) and high resolution transmission electron microscopy (HRTEM) confirm the single crystalline nature and much higher quality of the films on the latter substrates. Furthermore, no intermediate layer between the epilayer and substrate was observed for IBA on off-axis 4H-SiC. It is shown that the vicinal steps formed by hydrogen etching on the off-axis 4H-SiC substrate surface before deposition cause the film to adopt a single orientation, a process that is not seen on substrates with either no misorientation, or those tilted toward the [11- 20] direction. This work demonstrates that c-plane 4H-SiC with 7° offcut toward [1-100] is potentially a good substrate choice for the growth of high-quality, untwinned IBA epilayers for future device applications.
Keywords: Chemical vapor deposition; Epitaxy; Icosahedral boron arsenide; Crystal defects; Transmission electron microscopy; X-ray diffraction